The Significance of Soy Protein and Soy Bioactive Compounds in the Prophylaxis and Treatment of Osteoporosis - Sa'eed Bawa (Journal of Osteoporosis)
Osteoporosis is defined as a progressive systemic skeletal disease characterized by low bone mass and microarchitectural deterioration of bone tissue, with a consequent increase in bone fragility and susceptibility to fracture. Although bone mass and quality is mainly determined genetically, many other factors, including lifestyle and nutrition also have an impact on bone health. It has been suggested that dietary protein intake may be a risk factor for osteoporosis, and high-protein diets are associated with increased bone loss. Many scientists have examined the relationship between types of protein and urinary calcium excretion, and found that although animal protein was associated with increased urinary calcium excretion, soy protein was not. There is sufficient evidence suggesting soy isoflavones may have potential benefits for bone. Soy protein with naturally occurring phytoestrogens, mainly isoflavones protect against bone loss and synthetic soy ipriflavone in some studies has been shown to favorably affect, but a cause and effect relationship has not been established between the consumption of ipriflavone and maintenance of bone mineral density in post-menopausal women. Therefore it is too early to recommend it as a supplement for this group of women.